State of the world’s plants and fungi 2020 - Antonelli, A.; Fry, C.; Smith, R.J.; Simmonds, M.S.J.; Kersey, Paul J.; Pritchard, H.W.; Abbo, M.S.; Acedo, C.; Adams, J.; Ainsworth, A.M.; Allkin, B.; Annecke, W.; et al. (Royal Botanic Gardens, Kew, 2020)
Kew’s State of the World’s Plants and Fungi project provides assessments of our current knowledge of the diversity of plants and fungi on Earth, the global threats that they face, and the policies to safeguard them. Produced in conjunction with an international scientific symposium, Kew’s State of the World’s Plants and Fungi sets an important international standard from which we can annually track trends in the global status of plant and fungal diversity.